Indirect meta-analysis comparing clinical outcomes of total cervical disc replacements with fusions for cervical degenerative disc disease - Bin Xu (Nature Portfolio, 2017)
Abstract Anterior cervical discectomy and fusion (ACDF) and total cervical disc replacement (TDR) are considered effective treatments for patients with cervical degenerative disc disease (CDDD). An indirect meta-analysis including 19 randomized controlled trials (5343 patients) was conducted to compare the clinical outcomes of ACDF with TDR. Primary outcomes including functional indicators (NDI [neck disability index] score, neurological success and patient satisfaction), secondary outcomes including surgical outcomes (operation time, blood loss and length of stay) and secondary surgical procedures (secondary surgery at an adjacent level, secondary surgery at the index level, secondary surgery at both levels, removal, reoperation, revision and supplemental fixation) were included in the study. TDR using the Bryan disc was associated with a greater improvement in NDI score than ACDF (MD = −5.574, 95% CrIs [credible intervals] −11.73–−0.219). For neurological success, the Bryan (odds ratio [OR] = 0.559, 95% CrIs 0.323–0.955) and Prestige (OR = 0.474, 95% CrIs 0.319–0.700) discs were superior to ACDF. However, no differences in the patient satisfaction rate were shown between TDR and ACDF. For patients with CDDD, ACDF using allograft and a plate is most effective for determining the surgical parameters. Moreover, TDR using the ProDisc-C, Mobi-C, Prestige and Bryan discs are good choices for improving functional outcomes and reducing secondary surgeries.